(untitled) (Nordic Journal of Practical Theology, 2022)
Deacons within the Church of Norway constitute a professional group that can encounter older people’s need for existential conversations, but empirical research in this field is scarce. This study aims to explore professional deacons’ perceived competence in the field of older people and existential issues. Three focus group interviews with 18 deacons and an inductive qualitative content analysis were used to answer the inquiry. We introduce the term “approachable deacons” as an analytical innovation. Based on the empirical material and the perspectives from diaconia and the psychology of religion, arguments are made for the societal contribution of the deacon profession. As approachable existential conversation partners, deacons may make an essential contribution to public mental health. We assert that the deacon profession represents a counterculture to society and healthcare, where time is short, older people may feel downgraded, and existential and religious literacy is limited.